Effects of nutrition and physical exercise intervention in palliative cancer patients: A randomized controlled trial. Issue 4 (August 2018) - Uster, Alexandra; Ruehlin, Maya; Mey, Stefanie; Gisi, David; Knols, Ruud; Imoberdorf, Reinhard; Pless, Miklos; Ballmer, Peter E.
Summary: Background & aims: Cancer cachexia is multifactorial and should be targeted using a multimodal form of intervention. The purpose of the present trial was to test the effects of a combined nutrition and physical exercise program on cancer patients with metastatic or locally advanced tumors of the gastrointestinal and lung tracts. Methods: Patients were randomized into two groups: One group received a minimum of three standardized individual nutritional counselling sessions and participated in a 60-min exercise program twice a week. The second group received their usual care. The intervention spanned a period of three months. Quality of life (European Organization for Research and Treatment of Cancer Quality of Life Questionnaire version 3.0), physical performance (hand-grip strength, 6-min walk test, timed sit-to-stand test and 1 repetition maximum leg press), nutritional status (body weight, bioelectrical impedance analysis), dietary intake (three-day dietary record) and clinical data (unexpected hospital days, performance status) were tested at baseline and after three and six months. Results: In total, 18 women and 40 men (mean age 63, range 32–81) with metastatic or locally advanced tumors of the gastrointestinal ( n = 38) and lung ( n = 20) tracts were included. Median adherence to the supervised exercise program was 75%. The median number of individual nutritional counselling sessions was 3.0 (range 0–7 sessions). Post intervention, no difference in global health status/quality of life (overall QoL) was observed. Intervention was superior to UC for the patient-rated symptom scale regarding nausea and vomiting ( p = 0.023) and protein intake ( p = 0.01). No statistical differences were observed for energy intake, nutritional status and physical performance. Conclusions: The results show good adherence to a combined nutrition and exercise program. The multimodal intervention did not improve overall QoL, but contributed to an adequate protein intake and to the general well-being of the patient by reducing nausea and vomiting.